Réponses

Meilleure réponse !
2014-04-16T22:39:30+02:00
35) 1 : f(x)= 2/3x+1 donc ça fait f(3) = 2/3 x 3 + 1 = 6/3 + 1 = 2+1 = 3                                             2 : a) f(-3) = 2/3 x (-3) + 1 = -6/3 + 1 = -2 + 1 = -1                                                                            b) f(-1) =2/3 x (-1) +1 = -2/3 +1 = 1/3                                                                                          c) f(3/4)= 2/3 x 3/4 + 1 = 6/12 + 1 = 1/2 +2 3/2                                                                     36) 1 : g(x) = 0.4 x donc g(0) = 0.4 x 0 = 0                                                                                       2 ) g(5000) = 0.4 x 5000 = 2000